Photosensitizer spatial heterogeneity and its impact on personalized interstitial photodynamic therapy treatment planning - Saeidi, Tina; Wang, Shuran; Contreras, Hector A.; Daly, Michael J.; Betz, Vaughn; Lilge, Lothar (Journal of biomedical optics, 2025)
Personalized photodynamic therapy (PDT) treatment planning requires knowledge of the spatial and temporal co-localization of photons, photosensitizers (PSs), and oxygen. The inter- and intra-subject variability in the photosensitizer concentration can lead to suboptimal outcomes using standard treatment plans. We aim to quantify the PS spatial variation in tumors and its effect on PDT treatment planning solutions. The spatial variability of two PSs is imaged at various spatial resolutions for an orthotopic rat glioma model and applied to human glioblastoma models to determine the spatial PDT dose, including in organs at risk. An open-source interstitial photodynamic therapy (iPDT) planning tool is applied to these models, deriving the spatial photosensitizer quantification resolution that consistently impacts iPDT source placement and power allocation. The studies revealed a bimodal photosensitizer distribution in the tumor. The concentration of the PS can vary by a factor of 2 between the tumor core and rim, with slight variation within the core but a factor of 5 in the rim. An average sampling volume of for photosensitizer quantification will result in significantly different iPDT planning solutions for each case. Assuming homogeneous photosensitizer distribution results in suboptimal therapeutic outcomes, we highlight the need to predict the photosensitizer distribution before source placement for effective treatment plans.